Proceso atención de enfermería en adolescente con diabetes mellitus tipo 1. - Guapulema Vidal, Jose Luis (2021)
Type 1 diabetes mellitus is a severe disease that can become chronic if immediate treatment is not applied. It originally occurs in children and adolescents with a permanent increase in blood glucose as a particular feature. The Pan American Health Organization mentions that, in Ecuador, diabetes has gained strength and affects a considerable percentage of people, through surveys carried out by the INEC, the prevalence of the condition in the population between 11 and 60 years of age is 2%, which is why it is indicated that 3 out of 20 Ecuadorians already have the pathology. The present development of the clinical case of a 12-year-old female patient diagnosed with type I diabetes mellitus, in which the nursing care process was applied, at the time of admission to the hospital presented a clinical picture accompanied by thirst , general malaise, tiredness, nausea, dizziness, pain in the epigastrium, afebrile, hypotensive, mild tachypnea, hemodynamically unstable as far as the doctor refers to his hospital admission, additional tests are performed to determine the final diagnosis. Within the care established in the patient by the nursing professional, it was possible to apply the taxonomies of Nanda, Nic, Noc, likewise it was based on the theory of functional patterns designed by Gordon, M. which were used in a correct way to determine the needs presented by the patient according to their altered functional patterns.